A review of low head hydropower technologies and applications in a South African context. (October 2015) - Loots, I.; van Dijk, M.; Barta, B.; van Vuuren, S.J.; Bhagwan, J.N.
Abstract: This paper provides a review of available low head hydropower technologies, followed by the identification of sites where the technologies can be implemented, applied specifically to a South African context. The potential sites where low head hydropower can be installed in South Africa are grouped as follows: dams and barrages (retrofitting); rivers; irrigation systems (canals and conduits); and urban areas (industrial and urban discharge, storm water systems and water distribution systems).